Dissemination patterns of scientific abstracts presented at the first and second African Conference of Emergency Medicine - Marlin Abrams; Stevan R. Bruijns; Daniël J. van Hoving (African Journal of Emergency Medicine, 2019)
Introduction: Evidence based medicine is the standard of modern health care practices. Ongoing biomedical research is needed to expand existing knowledge and improve quality of care, but it needs to reach clinicians to drive change. Journal articles and conference presentations are dissemination tools. The aim of the study was to establish the publication rate of scientific abstracts presented at the first and second African Conference of Emergency Medicine. The secondary objectives were establishing non-publication dissemination and the factors associated with publication and non-publication. Determining non-publication dissemination patterns and the factors associated with reasons for publishing or non-publication were also investigated. Methods: Presenters of the 129 scientific abstracts from the first and second African Conference of Emergency Medicine were invited to participate in an online survey. The survey was followed by a manual literature search to identify published manuscripts of authors that did not complete the survey, to determine the most accurate publication rate. Results: Thirty-one presenters responded (24%), of which 18 published in a peer-reviewed journal. An additional 25 publications were identified by the literature search. The overall publication rate was 33.3% (26.9% from 2012 and 40.3% from 2014). Oral presentations were more likely to be published (p = 0.09). Sixteen manuscripts (37.2%) were published in the African Journal of Emergency Medicine. Presentations at local academic meetings were the most used platform beyond publication (43%). The main reason to publish was to add to the body of knowledge (100%), while lack of time (57%) was the major obstacle for not publishing. Conclusion: The overall publication rate for the first and second Africa Conferences of Emergency Medicine is comparable to other non-African Emergency Medicine conferences. The increasing publication trend between conferences might reflect the development of regional research capacity. Emergency Medicine providers in Africa need to be encouraged to participate in high quality, locally relevant research and to distribute those findings through accessible formats. Keywords: Conference, Africa, Publication, Barriers, Dissemination